2016
DOI: 10.1177/000313481608200316
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent Characteristics in Women with Breast Cancer: Mastectomy and Reconstructive Trends at an Urban Academic Institution

Abstract: Breast reconstruction is an important aspect of treatment after breast cancer. Postmastectomy reconstruction bears a significant impact on a woman's postsurgical confidence, sexuality, and overall well-being. Previous studies have inferred that women under age 40 years have unique characteristics that distinguish them from an older cohort. Identifying age-dependent trends will assist with counseling women on mastectomy and reconstruction. To identify age-dependent trends, 100 consecutive women were sampled fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Breast reconstruction is an oncologically safe procedure that improves the patient's self-esteem without increasing the risk of relapse or delaying the diagnosis of local recurrence (7). The reconstruction of the breast after mastectomy may preserve a woman's self-concept and improve her body image (23) and quality of life, resulting in a less traumatic rehabilitation process compared to that for mastectomy alone (24), especially among younger women, who give greater importance to body image than older women (25).…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction is an oncologically safe procedure that improves the patient's self-esteem without increasing the risk of relapse or delaying the diagnosis of local recurrence (7). The reconstruction of the breast after mastectomy may preserve a woman's self-concept and improve her body image (23) and quality of life, resulting in a less traumatic rehabilitation process compared to that for mastectomy alone (24), especially among younger women, who give greater importance to body image than older women (25).…”
Section: Discussionmentioning
confidence: 99%
“…The current results reveal that 77.7% of the unmatched and 81.8% of the matched patients were <50 years old, indicating that the preference for immediate breast reconstruction after mastectomy decreases with age. Studies have demonstrated that compared with older patients, younger patients with breast cancer are physiologically healthier, which makes them better candidates for breast reconstruction ( 7 , 31 ). Breast cancer in younger patients is likely to be more aggressive, leading to poorer quality of life and more mental health issues; however, the younger breast cancer cohort is also preferred for reconstructive options ( 7 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that compared with older patients, younger patients with breast cancer are physiologically healthier, which makes them better candidates for breast reconstruction ( 7 , 31 ). Breast cancer in younger patients is likely to be more aggressive, leading to poorer quality of life and more mental health issues; however, the younger breast cancer cohort is also preferred for reconstructive options ( 7 , 31 , 32 ). Moreover, the recent increase in the awareness and knowledge of, the increase in communication with professionals on and the development of decision support tools related to breast reconstruction may have also led to the increase in the preference for breast reconstruction among the younger breast cancer cohort ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age has been contended as a decisional influencer for RRM for women with breast cancer (Bhat, 2017; Chagpar, 2006; Elsayegh, 2018; Hoskins, 2012; Rodby, 2016). Literature also suggests that age factors into decision making for unaffected women.…”
Section: Discussionmentioning
confidence: 99%